Negative electrode active material particles, negative electrode comprising same, and secondary battery comprising same

By forming an aromatic cyclic monomer unit polymer coating containing alkyl groups and heteroatoms on the negative electrode active material particles of the secondary battery, the hydrogen generation problem caused by the reaction of water and silicon-based particles in the negative electrode slurry is solved, and the safety and performance of the battery are improved.

CN119547222APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056506.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the mixing of the negative electrode slurry of the secondary battery, the reaction between water and silicon-based particles leads to the production of hydrogen, and the carbon coating cannot effectively block the contact between moisture and silicon-based particles, which poses a safety hazard.

Method used

A polymer containing aromatic cyclic monomer units having alkyl groups at the side chains and containing heteroatoms is used as a coating to cover the core of the silicon-based particles, thereby inhibiting the reaction between water and silicon-based particles and reducing the generation of hydrogen.

Benefits of technology

It effectively reduces the production of hydrogen during the negative electrode slurry mixing process, improves the safety during the negative electrode manufacturing and battery driving process, and improves the battery life and fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547222A_ABST
    Figure CN119547222A_ABST
Patent Text Reader

Abstract

The present invention relates to negative electrode active material particles, a negative electrode comprising the negative electrode active material particles, and a secondary battery comprising the negative electrode. Specifically, the negative electrode active material particle is characterized by comprising a core and a coating layer provided on the core, the core comprising a silicon-based particle, and the coating layer comprising a polymer comprising an aromatic cyclic monomer unit having an alkyl group and comprising a heteroatom, thus, side reactions such as hydrogen generation can be prevented during aqueous mixing of the slurry without increasing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority of Korean Patent Application No. 10-2022-0110315 filed on August 31, 2022, in the Korean Intellectual Property Office, the contents of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a negative electrode active material particle, a negative electrode comprising the negative electrode active material particle, and a secondary battery comprising the negative electrode. Specifically, the negative electrode active material particle comprises a core and a coating layer located on the core, and the coating layer comprises a polymer, and the polymer comprises an aromatic cyclic monomer unit having an alkyl group at a side chain and containing a heteroatom. Background Art

[0004] With the rapid growth of fossil fuel use, there is an increasing demand for the use of alternative energy or clean energy, and as a part of this, the field of power generation and storage using electrochemical reactions is the most actively researched field.

[0005] In recent years, typical examples of electrochemical devices using electrochemical energy include secondary batteries, and the fields in which secondary batteries are used are gradually expanding. In recent years, with the technological development and increase in demand for portable devices such as portable computers, portable mobile phones, and cameras, the demand for secondary batteries as energy sources is rapidly increasing, and among secondary batteries, lithium secondary batteries with high energy density, i.e., high capacity, have been extensively studied, commercialized, and widely used.

[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that inserts and releases lithium ions from the positive electrode, and as the negative electrode active material, silicon-based particles having a large discharge capacity can be used.

[0007] On the other hand, the negative electrode can be formed by coating the negative electrode slurry on the negative electrode collector and drying. In this case, if water is used as a solvent to mix the negative electrode slurry containing silicon-based particles (hereinafter referred to as aqueous mixing), the silicon-based particles and water react to generate silicon dioxide and hydrogen. Hydrogen remains in the negative electrode slurry in the form of bubbles, and it is difficult to form a uniform negative electrode active material layer. In addition, the hydrogen remaining on the negative electrode is a flammable and explosive gas, and it can be very dangerous during the manufacturing process and driving process of the battery.

[0008] Conventionally, in order to overcome the above defects, a technique of forming a carbon coating on silicon-based particles is used. However, as time passes after the negative electrode slurry is formed, moisture may penetrate into the carbon coating, or oxygen may enter through cracks in the carbon coating, thereby causing a defect that the contact between moisture and silicon-based particles cannot be effectively blocked.

[0009] Therefore, the present invention provides a negative electrode active material particle and a method for preparing the negative electrode active material particle, which can minimize the generation of hydrogen during the mixing process of the negative electrode slurry. Summary of the invention

[0010] Technical issues

[0011] The task to be solved by the present invention is to provide a negative electrode active material particle which can minimize the generation of hydrogen during the mixing process of the negative electrode slurry.

[0012] Another task to be solved by the present invention is to provide a method for preparing the negative electrode active material particles.

[0013] Another task to be solved by the present invention is to provide a negative electrode comprising the negative electrode active material particles.

[0014] Another task to be solved by the present invention is to provide a secondary battery comprising the negative electrode.

[0015] Technical Solution

[0016] According to one embodiment of the present invention, there is provided a negative electrode active material particle, which comprises a core and a coating located on the core, wherein the core comprises a silicon-based particle, and the coating comprises a polymer, wherein the polymer comprises an aromatic cyclic monomer unit having an alkyl group at a side chain and comprising a heteroatom.

[0017] According to another embodiment of the present invention, there is provided a method for preparing negative electrode active material particles, comprising the step of putting core particles comprising silicon-based particles into a coating solution comprising a polymer comprising an aromatic cyclic monomer unit having an alkyl group at a side chain and comprising a heteroatom.

[0018] According to another embodiment of the present invention, a negative electrode is provided, comprising the negative electrode active material particles.

[0019] According to another embodiment of the present invention, a secondary battery including the negative electrode is provided.

[0020] Beneficial Effects

[0021] The negative electrode active material particles according to one embodiment of the present invention contain a coating layer containing a polymer on the surface of the core containing the silicon-based particles, the polymer containing an aromatic cyclic monomer unit having an alkyl group at the side chain and containing a heteroatom, which can inhibit the reaction between water and the silicon-based particles during the aqueous mixing process of the negative electrode slurry, and can minimize the generation of hydrogen. Therefore, the safety in the negative electrode manufacturing process and the battery driving process can be improved.

[0022] In addition, according to a method for preparing negative electrode active material particles in another embodiment of the present invention, a coating is formed on the core using a coating solution comprising a solvent and a polymer, wherein the polymer comprises an aromatic cyclic monomer unit having an alkyl group at the side chain and comprising a heteroatom, and the polymer comprising an alkyl chain at the side chain can be effectively coated on the core comprising silicon-based particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a schematic diagram showing negative electrode active material particles according to one embodiment of the present invention. DETAILED DESCRIPTION

[0024] Hereinafter, the present invention will be described in more detail to help understanding the present invention.

[0025] It should be understood that the words or terms used in the present invention and claims should not be interpreted as the meanings defined in commonly used dictionaries. It should also be understood that the words or terms should be interpreted as having meanings consistent with the technical ideas of the present invention on the basis that the inventor can appropriately define the meanings of the words or terms to best explain the principles of the present invention.

[0026] The terms used herein are only used to describe specific exemplary embodiments and are not intended to limit the concepts of the present invention. Unless the context clearly indicates otherwise, singular forms are intended to include plural forms as well.

[0027] It should also be understood that when used in this specification, the terms "comprising", "providing" or "having" are used to clarify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.

[0028] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume on the particle size distribution curve. The average particle size (D 50 ) can be measured, for example, using laser diffraction. Laser diffraction is generally capable of measuring diameters from the submicron range to several millimeters with high reproducibility and high resolution.

[0029] In this specification, "weight average molecular weight (Mw)" refers to a conversion value relative to standard polystyrene measured by gel permeation chromatography (GPC). In particular, the weight average molecular weight is a conversion value of a value measured using GPC under the following conditions, and a calibration curve is prepared using standard polystyrene of an Agilent system.

[0030] <Measurement conditions>

[0031] Measuring instrument: Agilent GPC (Agulent 1200 series, USA)

[0032] Column: Connect two PL Mixed B

[0033] Column temperature: 40°C

[0034] Eluent: Tetrahydrofuran

[0035] Flow rate: 1.0 mL / min

[0036] Concentration: ~1 mg / mL (100 μL injection)

[0037] In the present specification, the content (wt%) of the "polymer including an alkyl chain at a side chain" in the negative electrode active material particles can be confirmed by TGA. In this case, the measurement conditions are as follows.

[0038] Measuring instrument: Seiko Exstar 600 manufactured by Seiko Co.

[0039] Injection gas (atmospheric gas): Ar

[0040] Heating rate: 5℃ / min

[0041] Sample measurement amount: 10 mg

[0042] <Negative Electrode Active Material Particles>

[0043] refer to Figure 1 The negative electrode active material particle (10) comprises a core (100) and a coating (110) located on the core, wherein the core (100) comprises silicon-based particles, and the coating (110) may comprise a polymer comprising an aromatic cyclic monomer unit having an alkyl group at a side chain and containing a heteroatom.

[0044] The core may include silicon-based particles, and specifically, the core may be composed of silicon-based particles. If the core is a silicon-based particle, one silicon-based particle may correspond to one core.

[0045] The silicon-based particles may include SiO x (0≤x<2).SiOx (0≤x<2) may have a type containing Si and SiO2, and Si may form a phase. That is, x corresponds to SiO x (0≤x<2) is the ratio of the number of O to Si contained in the silicon-based particles. x (0≤x<2), the discharge capacity of the secondary battery can be increased. In particular, the silicon-based particles may be particles composed of Si.

[0046] The average particle size of silicon particles (D 50 ) may be 0.1 μm to 100 μm, particularly 1 μm to 10 μm, and more particularly 4 μm to 6 μm. If the range is satisfied, the internal and external reactions of the silicon-based particles during the battery driving process may be uniformly performed, and a pore structure in the negative electrode active material layer may be effectively formed, thereby achieving a uniform reaction in the negative electrode active material layer. Therefore, the life of the battery may be improved.

[0047] The coating may be located on the core. Specifically, the coating may cover at least a portion of the surface of the core.

[0048] The coating may include a polymer comprising an aromatic cyclic monomer unit having an alkyl group at the side chain and comprising a heteroatom. Because the coating includes a polymer comprising an aromatic cyclic monomer unit having an alkyl group at the side chain and comprising a heteroatom, if the negative electrode slurry containing the negative electrode active material particles is aqueously mixed, the reaction of the silicon-based particles of the core with water is suppressed, and the amount of hydrogen produced can be reduced. Therefore, the safety during the negative electrode manufacturing process and the battery driving process can be improved.

[0049] In the polymer, the alkyl group may be an alkyl group having 1 to 50 carbon atoms, preferably an alkyl group having 3 to 40 carbon atoms, an alkyl group having 3 to 30 carbon atoms, more preferably an alkyl group having 3 to 20 carbon atoms, particularly an alkyl group having 5 to 15 carbon atoms, and more particularly an alkyl group having 7 to 9 carbon atoms. If an alkyl group satisfying the above carbon number range is included as a side chain, the reaction between silicon-based particles and water during aqueous mixing of the negative electrode slurry can be more effectively suppressed, and the amount of hydrogen generated can be effectively reduced. In addition, because the alkyl group is not too long, the insertion and deinsertion of lithium ions at the negative electrode can be effectively achieved, and the capacity drop of the negative electrode active material particles can be minimized.

[0050] In addition, the polymer may contain one or more atoms selected from nitrogen (N), sulfur (S) and phosphorus (P), preferably one or more selected from nitrogen and sulfur. Compared with the case of containing only carbon, the heteroatom can provide surplus electrons, whereby the electrons can move freely via π-π bonds, thereby helping to improve conductivity. In addition, since the bonding force between the core of the silicon-based core and the polymer coating is insufficient, the coating separation phenomenon may occur, and thus it is preferred to use a polymer containing heteroatoms.

[0051] In addition, the polymer contains aromatic cyclic monomer units. Although the chain polymer is a conductive polymer, it may not be able to achieve the desired degree of conductivity if it is not additionally doped with atoms with high electronegativity. Despite the inclusion of heteroatoms, the flexibility of the main chain of the chain polymer may be higher than that of the case containing aromatic cyclic monomer units as basic units, and the polymer may tend to wrap around the surface of the core in a swollen state in the solvent during the coating process, and the absorption on the surface of the core may not be smooth, and the effect of improving conductivity or adhesion to the core may not be achieved. In the case of aliphatic cyclic monomer units, electrons may not move freely, which is not suitable.

[0052] The polymer containing an aromatic cyclic monomer unit containing an alkyl group at a side chain and containing a heteroatom may include at least one selected from the group consisting of a polymer containing a repeating unit of Formula 1, a polymer containing a repeating unit of Formula 2, and a polymer containing a repeating unit of Formula 3.

[0053] [Formula 1]

[0054]

[0055] [Formula 2]

[0056]

[0057] [Formula 3]

[0058]

[0059] In Formula 1, R1 and R2 are each independently one of hydrogen and an alkyl group having 5 to 15 carbon atoms, and at least one of R1 and R2 is an alkyl group having 5 to 15 carbon atoms. In Formula 1, the alkyl group having 5 to 15 carbon atoms may be specifically an alkyl group having 7 to 9 carbon atoms, more specifically -C8H 17 n1 may be an integer of 1 to 10,000, specifically an integer of 10 to 1,000, and more specifically an integer of 100 to 500. The polymer including the repeating unit of Formula 1 may be poly(3-octylthiophene) including the repeating unit of Formula 1-1.

[0060] [Formula 1-1]

[0061]

[0062] In Formula 2, R3 to R6 are each independently one of hydrogen and an alkyl group having 5 to 15 carbon atoms, and at least one of R3 to R6 is an alkyl group having 5 to 15 carbon atoms. In Formula 2, the alkyl group having 5 to 15 carbon atoms may be specifically an alkyl group having 7 to 9 carbon atoms, more specifically -C8H 17 n2 may be an integer of 1 to 10,000, specifically an integer of 10 to 1,000, and more specifically an integer of 100 to 500. The polymer including the repeating unit of Formula 2 may be a polymer including the repeating unit of Formula 2-1.

[0063] [Formula 2-1]

[0064]

[0065] In Formula 3, R7 to R 10 are each independently one of hydrogen and an alkyl group having 5 to 15 carbon atoms, and R7 to R 10 At least one of the above is an alkyl group having 5 to 15 carbon atoms. In Formula 3, the alkyl group having 5 to 15 carbon atoms may be particularly an alkyl group having 7 to 9 carbon atoms, more particularly -C8H 17 n3 may be an integer of 1 to 10,000, specifically an integer of 10 to 1,000, and more specifically an integer of 100 to 500. The polymer including the repeating unit of Formula 3 may be a polymer including the repeating unit of Formula 3-1.

[0066] [Formula 3-1]

[0067]

[0068] That is, the polymer containing an aromatic cyclic monomer unit having an alkyl group at the side chain and containing a heteroatom may include poly (3-octylthiophene) or poly (3-octylpyrrole), preferably, the polymer containing an aromatic cyclic monomer unit having an alkyl group at the side chain and containing a heteroatom may be poly (3-octylthiophene). If a polymer selected from Formula 1-1 to Formula 3-1 is included as the polymer containing an aromatic cyclic monomer unit having an alkyl group at the side chain and containing a heteroatom, the reaction between the silicon-based particles and water during the aqueous mixing process of the negative electrode slurry can be more effectively suppressed, and the amount of hydrogen generated can be significantly reduced. In addition, because the polymer has high conductivity, the conductivity in the negative electrode can be improved, thereby improving the life and fast charging performance of the battery.

[0069] The weight average molecular weight of the polymer containing an aromatic cyclic monomer unit having an alkyl group at the side chain and containing a heteroatom may be 200 g / mol to 2,000,000 g / mol, particularly 2,000 g / mol to 200,000 g / mol, more particularly 10,000 g / mol or more, 15,000 g / mol or more, 20,000 g / mol or more, or 25,000 g / mol or more, and 150,000 g / mol or less, 130,000 g / mol or less, 100,000 g / mol or less, or 90,000 g / mol or less. If the above range is met, the polymer containing an aromatic cyclic monomer unit having an alkyl group at the side chain and containing a heteroatom may be uniformly coated on the entire surface of the silicon-based particles, and agglomeration of the polymer with the silicon-based particles during the preparation of the negative electrode active material may be prevented.

[0070] The content of the polymer containing an alkyl chain at the side chain in the negative electrode active material particles can be 0.1% by weight to 50% by weight, especially 1.0% by weight or more, 3.0% by weight or more, 4.0% by weight or more, 5.0% by weight or more, 6.0% by weight or more, or 7.0% by weight or more and 30% by weight or less, 25% by weight or less, 20% by weight or less, 18% by weight or less, 15% by weight or less, or 12% by weight or less. If the above range is met, the capacity per unit weight of the negative electrode active material particles can be maintained at an appropriate level, lithium ions can be easily diffused into the core, and the life of the negative electrode and the battery can be improved.

[0071] The average particle size of the negative electrode active material particles (D 50 ) can be 0.1 μm to 150 μm, particularly 1 μm to 20 μm, more particularly 3 μm to 10 μm, for example 5 μm to 7 μm. If the above range is met, the generation of gas during the preparation of the negative electrode slurry can be effectively suppressed, and the life and fast charging performance of the battery can even be further improved.

[0072] <Method for preparing negative electrode active material particles>

[0073] A method of preparing negative electrode active material particles according to another embodiment of the present invention may include the step of putting core particles including silicon-based particles into a coating solution including a solvent and a polymer including an alkyl chain at a side chain.

[0074] Here, the negative electrode active material particles may be the same as the negative electrode active material particles of the above-mentioned embodiment. In addition, the core particles may correspond to the core contained in the negative electrode active material particles of the above-mentioned embodiment. In addition, the polymer containing an alkyl chain at the side chain may correspond to the polymer containing an alkyl chain at the side chain of the above-mentioned embodiment. Therefore, its description will be omitted. The polymer containing an alkyl chain at the side chain may be provided on the core particles, and the coating described in the above-mentioned embodiment may be formed.

[0075] The coating solution may include a solvent and a polymer including an alkyl chain at a side chain.

[0076] The solvent may include at least one selected from chloroform, toluene, hexane, benzene and tetrahydrofuran. The polymer comprising an alkyl chain at the side chain exhibits hydrophobicity. Therefore, if the solvent includes at least one selected from chloroform, toluene, hexane, benzene and tetrahydrofuran, the polymer comprising an alkyl chain at the side chain can be effectively dispersed in the solvent. Thus, the coating can have a uniform thickness and can be stably formed.

[0077] After the inputting step, the coating solution including the silicon-based particles may be stirred to place the polymer including an alkyl chain at a side chain on the silicon-based particles.

[0078] <Negative electrode>

[0079] The negative electrode according to another embodiment of the present invention may include negative electrode active material particles. Here, the negative electrode active material particles may be the same as the negative electrode active material particles of the above embodiment. In particular, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include negative electrode active material particles. In addition, the negative electrode active material layer may further include a negative electrode binder and / or a negative electrode conductive material.

[0080] The negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the battery and has conductivity. For example, the current collector may use: copper, stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. In particular, transition metals such as copper and nickel that can adsorb carbon well can be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but the thickness of the current collector is not limited thereto.

[0081] The negative electrode binder may include at least one selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by Li, Na or Ca, and may also include various copolymers thereof.

[0082] There is no specific limitation on the negative electrode conductive material as long as it does not cause chemical changes in the battery and has conductivity, and may include, for example: graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0083] <Secondary Battery>

[0084] A secondary battery according to another embodiment of the present invention may include the negative electrode of the above embodiment. In particular, the secondary battery may include a negative electrode, a positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above negative electrode. Since the negative electrode has been described above, its specific description will be omitted.

[0085] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material.

[0086] In the positive electrode, there is no specific limitation on the positive electrode collector, as long as it does not cause chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and the adhesion of the positive electrode active material can be enhanced by forming fine concave-convex on the surface of the collector. For example, various shapes including films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc. can be used.

[0087] The positive electrode active material may be a commonly used positive electrode active material. In particular, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 or Cu2V2O7, etc.; 1-c2 M c2 O2 (herein, M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and 0.01≤c2≤0.3) Ni-site lithium nickel oxide represented by LiMn 2-c3 M c3 The positive electrode may be a lithium manganese composite oxide represented by Li2Mn3MO8 (herein, M is at least one selected from the following: Co, Ni, Fe, Cr, Zn and Ta, and 0.01≤c3≤0.1); or Li2Mn3MO8 (herein, M is at least one selected from the following: Fe, Co, Ni, Cu and Zn); or LiMn2O4 in which a portion of Li is replaced by an alkaline earth metal ion, etc., but is not limited thereto. The positive electrode may be a Li metal.

[0088] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0089] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and any material may be used without specific limitation as long as it does not cause chemical changes in the battery and has conductivity in the battery. Specific examples may include: graphite such as natural graphite and artificial graphite; carbonaceous materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; conductive polymers such as polyphenylene derivatives, and a single material or a mixture of two or more thereof may be used.

[0090] In addition, the positive electrode binder plays a role in improving the adhesion between the positive electrode active material particles and between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and a single material or a mixture of two or more thereof may be used.

[0091] As a separator, a separator commonly used in a secondary battery can be used without particular limitation, the separator separating the negative electrode from the positive electrode and providing a mobile channel for lithium ions, in particular, a separator having low resistance to the movement of electrolyte ions and excellent absorption capacity for the electrolyte is preferred. In particular, a porous polymer film, such as a porous polymer film formed by a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a stacked structure of two or more layers thereof can be used. In addition, commonly used porous non-woven fabrics can be used, such as non-woven fabrics of glass fibers with high melting points, polyethylene terephthalate fibers, and the like. In addition, in order to ensure heat resistance and mechanical strength, a coated separator comprising a ceramic component or a polymer material can be optionally used in a single-layer or multi-layer structure.

[0092] The electrolyte may include, without limitation, an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten-type inorganic electrolyte, and the like, which can be used when manufacturing a lithium secondary battery.

[0093] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0094] The non-aqueous organic solvent may use an aprotic organic solvent, such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, and the like.

[0095] Especially, in carbonate organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are organic solvents with high viscosity and high dielectricity, can dissociate lithium salts well and are preferably used.If linear carbonates such as dimethyl carbonate and diethyl carbonate with low viscosity and low dielectricity are mixed and used with cyclic carbonate in appropriate ratio, then electrolyte with high conductivity can be formed, which is preferably used.

[0096] The metal salt may be a lithium salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte, and the anion of the lithium salt may be one or more selected from the following: - , Cl - ,I - 、NO3 -、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0097] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity and increase the discharge capacity of the battery, in the electrolyte, on the basis of the constituent components of the electrolyte, one or more additives may be further included. For example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0098] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. The battery module and the battery pack include secondary batteries having high capacity, high rate performance and cycle performance, and can be used as a power source for medium and large devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0099] Hereinafter, preferred embodiments will be proposed to help understand the present invention, but the embodiments are merely illustrative of this specification, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of this specification, and these changes and modifications are also included in the claims attached hereto.

[0100] Examples and Comparative Examples

[0101] Example 1: Preparation of negative electrode active material particles

[0102] A coating solution was prepared in which 10 g of poly(3-octylthiophene) containing a repeating unit of Formula 1-1 was dispersed in 50 g of chloroform. In addition, an average particle size (D 50 ) with a diameter of 5 μm as core particles.

[0103] [Formula 1-1]

[0104]

[0105] The core particles were put into the coating solution and stirred for 2 hours using a magnetic bar and a magnetic stirrer to prepare negative electrode active material particles.

[0106] The average particle size of the negative electrode active material particles (D 50 ) was 6 μm, and the weight average molecular weight of poly(3-octylthiophene) was 30,000. In addition, the content of poly(3-octylthiophene) in the negative electrode active material particles was 6 wt %.

[0107] Example 2: Preparation of negative electrode active material particles

[0108] Negative electrode active material particles were prepared by the same method as in Example 1, except that the content of poly(3-octylthiophene) in the negative electrode active material particles was controlled to 12 wt %.

[0109] Example 3: Preparation of negative electrode active material particles

[0110] Negative active material particles were prepared by the same method as in Example 1, except that a polymer including a repeating unit of Formula 2-1 and having a weight average molecular weight of 30,000 was used instead of poly(3-octylthiophene).

[0111] [Formula 2-1]

[0112]

[0113] Example 4: Preparation of negative electrode active material particles

[0114] Negative electrode active material particles were prepared by the same method as in Example 3, except that the content of the polymer including the repeating unit of Formula 2-1 in the negative electrode active material particles was controlled to 7 wt %.

[0115] Example 5: Preparation of negative electrode active material particles

[0116] Negative active material particles were prepared by the same method as in Example 1, except that a polymer including a repeating unit of Formula 3-1 and having a weight average molecular weight of 30,000 was used instead of poly(3-octylthiophene).

[0117] [Formula 3-1]

[0118]

[0119] Example 6: Preparation of negative electrode active material particles

[0120] Negative electrode active material particles were prepared by the same method as in Example 3, except that the content of the polymer including the repeating unit of Formula 3-1 in the negative electrode active material particles was controlled to 7 wt %.

[0121] Example 7: Preparation of negative electrode active material particles

[0122] Negative electrode active material particles were prepared by the same method as in Example 1, except that the content of poly(3-octylthiophene) in the negative electrode active material particles was controlled to 5 wt %.

[0123] Example 8: Preparation of negative electrode active material particles

[0124] Negative electrode active material particles were prepared by the same method as in Example 1, except that the content of poly(3-octylthiophene) in the negative electrode active material particles was controlled to 7 wt %.

[0125] Example 9: Preparation of negative electrode active material particles

[0126] Negative electrode active material particles were prepared by the same method as in Example 1, except that the content of poly(3-octylthiophene) in the negative electrode active material particles was controlled to 9 wt %.

[0127] Example 10: Preparation of negative electrode active material particles

[0128] Negative electrode active material particles were prepared by the same method as in Example 1 except that poly(3-octylthiophene) having a weight average molecular weight of 20,000 was used.

[0129] Example 11: Preparation of negative electrode active material particles

[0130] Negative electrode active material particles were prepared by the same method as in Example 1 except that poly(3-octylthiophene) having a weight average molecular weight of 100,000 was used.

[0131] Comparative Example 1: Preparation of Negative Electrode Active Material Particles

[0132] The average particle size (D 50 ) is 5 μm silicon particles as negative electrode active material particles.

[0133] Comparative Example 2: Preparation of Negative Electrode Active Material Particles

[0134] A coating solution was prepared in which 10 g of polythiophene containing no alkyl chain at the side chain was dispersed in 50 g of chloroform. In addition, an average particle size (D 50 ) with a diameter of 5 μm as core particles.

[0135] The core particles were put into the coating solution and stirred for 2 hours using a magnetic bar and a magnetic stirrer to prepare negative electrode active material particles.

[0136] The average particle size of the negative electrode active material particles (D 50 ) was 6 μm, and the weight average molecular weight of polythiophene was 20,000. In addition, the content of polythiophene in the negative electrode active material particles was 5% by weight.

[0137] Comparative Example 3: Preparation of Negative Electrode Active Material Particles

[0138] Negative electrode active material particles were prepared in the same manner as in Example 1 except that a polymer containing an octyl group as a side chain in polyethyleneimine was used instead of poly(3-octylthiophene).

[0139] Comparative Example 4: Preparation of Negative Electrode Active Material Particles

[0140] Negative electrode active material particles were prepared in the same manner as in Example 1 except that a polymer containing octyl groups as side chains in polyacetylene was used instead of poly(3-octylthiophene).

[0141] Comparative Example 5: Preparation of Negative Electrode Active Material Particles

[0142] Negative electrode active material particles were prepared by the same method as in Example 1, except that poly(p-phenylenevinylene-2,5-dioctyl-p-phenylenevinylene) was used instead of poly(3-octylthiophene).

[0143] Comparative Example 6: Preparation of Negative Electrode Active Material Particles

[0144] Negative electrode active material particles were prepared by the same method as in Example 1, except that poly(1,4-piperazinediyl-1-oxytrimethylene) was used instead of poly(3-octylthiophene).

[0145] Experimental Example 1: Evaluation of the compressive conductivity of negative electrode active material particles

[0146] The compressive conductivity of the negative electrode active material particles was evaluated by the following method.

[0147] A plurality of negative electrode active material particles in a fine particle state were compressed into a cylindrical shape, while current was applied to flow through the top and bottom of the compressed negative electrode active material particle sample, and the conductivity of the compressed negative electrode active material particle was measured.

[0148] Measuring instrument: HPRM-FA2 from HANTECH Co.

[0149] Sample loading: 3 g

[0150] Injector diameter: 20 mm

[0151] Pressing pressure: 2,000 kgf / cm 2

[0152] Applied voltage to sample: 10 V

[0153] Experimental Example 2: Evaluation of Hydrogen Generation Amount of Negative Electrode Slurry

[0154] Using the negative electrode active material particles of the embodiment and the comparative example, negative electrode slurry was prepared. Specifically, the negative electrode active material particles, the binder CMC, the conductive material Super 65 and the single-walled carbon nanotubes were put into water at a ratio of 80:9:10:1 to prepare a mixture, and the mixture was dispersed at a rate of 2,500 rpm for 60 minutes using a homogenizer to prepare a negative electrode slurry (solid content of 30%).

[0155] In a thermostatic box at 40° C., 4 g of the negative electrode slurry was placed in a 5 ml measuring container, and the amount of hydrogen generated was evaluated using a gas manometer. The results are shown in Table 1.

[0156] Experimental Example 3: Evaluation of Lifespan (Capacity Retention Rate)

[0157] Negative electrodes and batteries were manufactured using the negative electrode active materials of Examples and Comparative Examples.

[0158] Using the negative electrode active material particles of the embodiment and the comparative example, negative electrode slurry was prepared. Specifically, the negative electrode active material particles, the binder CMC, the conductive material Super 65 and the single-walled carbon nanotube were put into water at a ratio of 80:9:10:1 to prepare a mixture, and the mixture was dispersed at a rate of 2,500 rpm for 60 minutes using a homogenizer to prepare a negative electrode slurry.

[0159] The negative electrode slurry was coated on a 20 μm thick copper (Cu) metal film as a negative electrode current collector and dried. In this case, the temperature of the circulating air was 60° C. It was then roll-pressed and dried in a vacuum oven at 130° C. for 12 hours to produce a negative electrode.

[0160] The negative electrode thus prepared and the positive electrode cut into 1.7671 cm 2 A circular lithium (Li) metal film is formed. A porous polyethylene separator is provided between the positive electrode and the negative electrode, and an electrolyte is injected therein to manufacture a lithium coin half-cell, wherein in the electrolyte, 0.5 wt % of vinylene carbonate is dissolved in a mixed solution of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a volume ratio of 7:3, and 1 M concentration of LiPF6 is also dissolved.

[0161] The battery was charged and discharged, and the capacity retention rate was evaluated, and the results are shown in Table 1.

[0162] At the 1st and 2nd cycles, charging and discharging were performed at 0.1 C, and at the 3rd to 49th cycles, charging and discharging were performed at 0.5 C. The 300th cycle was completed in a charged state (a state in which lithium is contained in the negative electrode), the battery was disassembled, the thickness was measured, and the thickness change of the electrode was calculated.

[0163] Charging conditions: CC (constant current) / CV (constant voltage) (5 mV / 0.005 C current cutoff)

[0164] Discharge condition: CC (constant current) condition 1.5 V

[0165] The capacity retention rate was calculated as follows.

[0166] Capacity retention rate (%) = (discharge capacity of the 50th cycle / discharge capacity of the first cycle) × 100

[0167]

[0168] Referring to Table 1, in Examples 1 to 11 to which the negative electrode active material particles according to the present invention are applied, it can be confirmed that the compression conductivity, hydrogen generation amount and capacity retention rate are all evaluated as excellent. On the contrary, in Comparative Example 1 in which no coating is formed, it can be found that the conductivity is low, a side reaction of generating a large amount of hydrogen occurs, and the life characteristics are evaluated as poor. In Comparative Example 2 in which a polymer not containing an alkyl group at the side chain is applied, it is confirmed that the conductivity is improved, but the defect of generating hydrogen is not resolved, and the life characteristics are still poor.

[0169] In addition, considering Comparative Examples 3 and 4 in which a chain monomer unit is used as a polymer of the coating layer, in the case of Comparative Example 4, it can be confirmed that the conductivity is significantly poor, the conductivity is not better than the poor level despite the inclusion of heteroatoms, and the limitation of the chain shape is not overcome. Compared with the example in which the aromatic cyclic monomer is applied, the adhesion between the coating layer and the core is low, the separation phenomenon of the coating layer occurs, and the amount of gas generated is large.

[0170] In addition, in the case of Comparative Example 5, which differs from the Examples in that no heteroatom is included, it can be confirmed that the free electrons moving through the π-π bonds of the main chain are insufficient and the conductivity is poor. In the case of Comparative Example 6, which contains heteroatoms but uses an aliphatic cyclic monomer unit, it can be confirmed that the conductivity is significantly poor because there is no π-π bond in the main chain.

[0171] From the above discussion, it can be found that, in the case where silicon-based particles are used as negative electrode active materials, it is preferred that the polymer according to the present invention is used as a coating of the silicon-based particles, thereby preventing side reactions such as the generation of hydrogen during the preparation of the aqueous slurry and improving conductivity and life.

Claims

1. A negative electrode active material particle, comprising a core and a coating layer on the core, wherein the core comprises silicon-based particles, and The coating layer includes a polymer including an aromatic cyclic monomer unit having an alkyl group at a side chain and including a heteroatom. 2 . The negative electrode active material particle according to claim 1 , wherein the alkyl group is an alkyl group having 1 to 50 carbon atoms. 3 . The negative electrode active material particle according to claim 1 , wherein the heteroatom is one or more selected from nitrogen (N), sulfur (S) and phosphorus (P).

4. The negative electrode active material particle according to claim 1, wherein The heteroatom is one or more selected from nitrogen (N) and sulfur (S), and The alkyl group is an alkyl group having 3 to 20 carbon atoms.

5. The negative electrode active material particle according to claim 1, wherein the polymer comprises at least one selected from the group consisting of a polymer comprising a repeating unit of the following formula 1, a polymer comprising a repeating unit of the following formula 2, and a polymer comprising a repeating unit of the following formula 3, [Formula 1] [Formula 2] [Formula 3] In Formula 1, R1 and R2 are each independently one of hydrogen and an alkyl group having 5 to 15 carbon atoms, at least one of R1 and R2 is an alkyl group having 5 to 15 carbon atoms, and n1 is an integer of 1 to 10,000, In Formula 2, R3 to R6 are each independently one of hydrogen and an alkyl group having 5 to 15 carbon atoms, at least one of R3 to R6 is an alkyl group having 5 to 15 carbon atoms, and n2 is an integer of 1 to 10,000, and In Formula 3, R7 to R 10 are each independently one of hydrogen and an alkyl group having 5 to 15 carbon atoms, R7 to R 10 At least one of is an alkyl group having 5 to 15 carbon atoms, and n3 is an integer from 1 to 10,000. 6 . The negative electrode active material particle according to claim 1 , wherein the weight average molecular weight of the polymer is 200 g / mol to 2,000,000 g / mol. 7 . The negative electrode active material particle according to claim 1 , wherein a content of the polymer in the negative electrode active material particle is 0.1 wt % to 50 wt %.

8. The negative electrode active material particles according to claim 1, wherein the average particle size (D 50 ) is 0.1 μm to 100 μm. 9 . A negative electrode, comprising the negative electrode active material particles according to claim 1 . 10 . A secondary battery comprising the negative electrode according to claim 9 .

Citation Information

Patent Citations

  • Determination of hole size within the fuel tank system

    KR1020220110315A